Passive Seismology: Lightweight and Rapid Detection of Arctic Subsea and Sub‐Aquatic Permafrost ... - Angelopoulos, Michael; Ryberg, Trond; Rasmussen, Christian Frigaard; Haberland, Christian; Juhls, Bennet; Dallimore, Scott; Boike, Julia; Overduin, Pier Paul (Humboldt-Universität zu Berlin, 2024)
Low sea levels during the last Ice Age exposed millions of square kilometers of Arctic shelves which have been subsequently submerged, creating subsea permafrost. In onshore settings, permafrost can also exist beneath water bodies such as coastal lagoons, rivers, and thermokarst lakes. We explored passive seismology as a method for mapping unfrozen sediment thickness above subsea and sub‐aquatic permafrost. We present passive seismic data collected with the Mobile Ocean Bottom Seismic Instrument (MOBSI) from the Beaufort Sea near Tuktoyaktuk in Canada, Ivashkina Lagoon on the Bykovsky Peninsula, as well as a lake and river in the Lena Delta, Siberia, Russia. We use borehole data and frost probe measurements to identify permafrost‐related H/V measurement peaks and calibrate shear wave velocities for frequency‐to‐depth conversion. We employ the shortest path and maximum signal amplitude to connect peaks and generate geological profiles. The MOBSI detected the ice‐bonded permafrost table beneath the Beaufort ...